2016
DOI: 10.1021/acsnano.5b08025
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylpyrrolidone–Poly(ethylene glycol) Modified Silver Nanorods Can Be a Safe, Noncarrier Adjuvant for HIV Vaccine

Abstract: One of the biggest obstacles for the development of HIV vaccines is how to sufficiently trigger crucial anti-HIV immunities via a safe manner. We herein integrated surface modification-dependent immunostimulation against HIV vaccine and shape-dependent biosafety and designed a safe noncarrier adjuvant based on silver nanorods coated by both polyvinylpyrrolidone (PVP) and polyethylene glycol (PEG). Such silver nanorods can significantly elevate crucial immunities of HIV vaccine and overcome the toxicity, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…[265] Worse still, the HIV virus could only be reduced but not completely removed from infected patients. [251] The authors had a preference for NRs but not nanospheres mainly due to safety consideration. However, the immunity generated by neutralizing Abs targeting HIV envelope glycoproteins is far from satisfactory.…”
Section: Nanoparticle Vaccine For Hivmentioning
confidence: 99%
“…[265] Worse still, the HIV virus could only be reduced but not completely removed from infected patients. [251] The authors had a preference for NRs but not nanospheres mainly due to safety consideration. However, the immunity generated by neutralizing Abs targeting HIV envelope glycoproteins is far from satisfactory.…”
Section: Nanoparticle Vaccine For Hivmentioning
confidence: 99%
“…This synergism has improved antimicrobial effects against microbial strains including Staphylococcus aureus , Micrococcus luteus , Salmonella typhi , and Escherichia coli compared to the activity of these antibiotics alone. In addition, Liu et al27 developed modified silver nanorods with polyvinylpyrrolidone–polyethylene glycol (PEG) as a candidate for adjuvant human immunodeficiency virus vaccine delivery owing to its safety and low toxicity in biological systems compared to silver nitrates, which exhibit toxicity at 2 μg/mL 8,28. Erick and Padmanabhan29 showed that AgNPs synthesized by green methods have exhibited high larvicidal and pupicidal activity against the malarial vector Anopheles stephensi .…”
Section: Introductionmentioning
confidence: 99%
“…We synthesize two types of silver NMs with the same surface modification of polyvinylpyrrolidone (PVP) and polyethylene glycol (PEG), diameter (60 nm), charge (−11 mV), and size/volume, but different shapes (rod and sphere). By inductively coupled plasma spectroscopy and transmission electron microscope, we observe that the uptake of nanorods by Hela and HUVEC cell lines are far less than nanospheres in a broad concentration range ( Figure ) . Such a result is also indirectly verified in vivo via evaluating the toxicity of NMs that is correlated with NMs cellular uptake.…”
Section: Shapementioning
confidence: 57%
“…There is a linear relationship between the cytotoxicity and the uptake of NM. Reproduced with permission . Copyright 2016, American Chemical Society.…”
Section: Shapementioning
confidence: 99%
See 1 more Smart Citation